Kinetics and performance of coagulation process using Mucuna seed shell for the treatment of paint wastewater. Issue 4 (2nd October 2018) - Nwabanne, Joseph Tagbo; Oguegbu, Ozioma Onyinye; Agu, Chinedu Matthew
Abstract: The use of coagulation technique in the treatment of different kinds of wastewaters has been employed using various coagulants. In this study, the focus is on the efficiency of coagulation process in the treatment of paint wastewater (PW) using Mucuna seed shell (MSS) as a natural and cost effective coagulant. The effluent was collected from a paint industry in Enugu State, Nigeria. Effects of initial pH, settling time, coagulant dosage, and temperature were studied. Results show that there was a drastic reduction in the suspended and dissolved particles (SDP) in the effluent. Removal of SDP was found to be dependent on the process variables of initial pH, settling time, coagulant dosage and temperature. The highest removal efficiency of 95% was obtained at coagulant dosage of 2500 mg/L, time of 30 min and temperature of 30 °C. The particle distribution plot shows decrease in the normalized number of total particles as a function of time. Among the two kinetic models that were studied, the process was observed to follow the second-order coagulation kinetics. From this study, it can be concluded that the use of MSS coagulant was effective in the treatment of PW.